A probiotic intervention on pain hypersensitivity and microbiota composition in patients with osteoarthritis pain: Study protocol for a randomized controlled trial - Paolo Pedersini,; Marco Savoldi,; Pedro Berjano,; Jorge Hugo Villafañe, (Archives of Rheumatology, 2021)
Objectives: This study aims to examine the effects of probiotics on pain hypersensitivity at the end of a six-week intervention program in patients with osteoarthritis (OA)-related pain. Patients and methods: This double-blind randomized controlled clinical trial with two parallel arms will be conducted between January 2021 and July 2022. At least 30 participants (age range, 50 to 90 years) of both sexes with a diagnosis of symptomatic hip or knee (Kellgren-Lawrence scale ≥3) will be recruited in each arm (total n=60) to achieve adequate statistical power in the analyses. The intervention will be administered for six weeks followed by a four-week follow-up period. The experimental group will receive a probiotic product plus the usual medical care. The control group will receive a probiotical sham plus the usual medical care. Assessment points will be measured at baseline, end of intervention, and one-month post-intervention. The outcomes of this intervention will be a change in visual analog scale pain and the gut microbiota composition. Group by time effects will be compared using mixed-model analysis of variance. Conclusion: A reduction in pain hypersensitivity in patients with knee OA-related pain could suggest an involvement of microbiota, or part of it, in chronic pain state mechanisms.